FUNGSI PELAKSANAAN SINKRONISASI ADMINISTRASI CONTAINER DI CV KAY ALOR SEJAHTERA JAKARTA UTARA - Sheila Ananda Choirunisa; Koerniawan Hidajat (Jurnal Abdimas Bina Bangsa, 2023)
This journal discusses the function of implementing administrative synchronization related to the management of container units at the CV. Kay Alor Sejahtera North Jakarta. Container or Container is a rectangular box with a special design, has a certain size made of iron or aluminum, with a door on one side and can be used many times, besides being used as a place to store and transport goods from one place to another. And has been identified according to international standards (ISO) Container or container can also be modified into a semi-residential where it functions as a temporary residence. Containers are an important component of a company's logistics operations, and effective administration is necessary to maintain a smooth turnover of goods, avoid delays, and optimize the use of Container units. The purpose of this research is to analyze and document the various administrative functions related to Container management both sales and rental of each type of Container, as well as provide concrete examples of implementation in the company CV. Kay Alor Sejahtera